Understanding the consequences of workplace incivility: the roles of emotional exhaustion, acceptability and political skill. Issue 3 (20th January 2022) - Moon, Chanki; Morais, Catarina
Abstract : Purpose: Workplace incivility is a common deviant behavior happening in organizational contexts, and it can have serious negative consequences such as decreasing employees' organizational citizenship behavior (OCB) and increasing their turnover intentions. This study aims to test the argument that emotional exhaustion and acceptability of workplace incivility can act as mediators in this relationship between incivility and OCB and turnover intentions. Moreover, the assumption that employees' political skill can act as a buffer on job strain caused by incivility displayed by both coworkers and supervisors was tested. Design/methodology/approach: In total, 703 South Korean employees recruited online completed a self-assessment on their political skill first and then they were randomly assigned to one of the two conditions: either recalled a co-worker or a supervisor who had previously displayed uncivil behaviors toward them. Findings: The stronger the employees' experience of incivility, the lower their OCB-O and the higher their turnover intentions. These relationships were mediated by acceptability of incivility and emotional exhaustions. Interestingly, results also supported the moderating role of political skill on the relationship between incivility and turnover intentions mediated by acceptability, with higher politically skilled employees being more likely to accept incivility when compared to lower politically skilled employees. Originality/value: Using a between-subjects design, the findings expand the current knowledge regarding the negative impacts of workplace incivility. Specifically, they showed that acceptability is an important mechanism to understand the impact of workplace incivility on OCB and turnover intention.